Model for developing audio visual media efforts to increase religion and moral values of early age children kota Bengkulu - Margaretha, Lydia (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
This study aims to: (1) Design audio-visual media development that can enhance religious and moral values in learning; (2) Describe the effectiveness of using audio-visual media to improve religious and moral values. The subjects of this study were class B teachers and children in the B grade of Bengkulu City. While the object of this research is audio-visual media as a learning medium in aspects of religious and moral values. This research was carried out using a "Research and Development" approach. Conclusions are taken: (1) Audiovisual media as learning media that can explain abstract religious and moral values to be concrete and attract children's attention so that they can increase religious and moral values child. (2) The audio-visual media developed is an effective alternative media as a learning media for aspects of religious and moral values to enhance the religious and moral values of Class B PAUD children. Increased religious values are significantly based on the results of ttest level significance 0.00 which is smaller than 5%. The use of audio-visual media can improve children's morale after using audio-visual media is higher than before using audio-visual media.